Ticking the box of ‘cultural safety’ is not enough: why trauma-informed practice is critical to Indigenous healing - Nicole Tujague; Kelleigh Ryan (James Cook University, 2021)
It is critical that those working with Aboriginal and Torres Strait Islander communities acknowledge and understand the impacts of trauma in order to engage in culturally safe practice. Recognising the role that historical and other traumas play in Indigenous people's communities and lives is a prerequisite for respectful and safe practice. Culturally safe, trauma-informed practice training makes cultural safety more achievable. Organisations that are serious about working and partnering with Aboriginal and Torres Strait Islander peoples are becoming 'trauma informed'. Aboriginal and Torres Strait Islander peoples are drawing immense strength and hope from understanding trauma and its impact on their lives. Sharing this knowledge with Aboriginal and Torres Strait Islander populations also has the potential to create safe healing spaces and interrupt trauma being passed on through generations. Trauma-informed cultural safety can allow profound change for individuals and the systems within which they practice.